Correlation Between Metacognitive Listening Awareness and Listening Comprehension in EFL Students - Putri Khurnia Sikumbang; Juwita Boneka Sinaga; Erwin Ashari (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2026)
Listening comprehension remains one of the most challenging yet essential skills in English as a Foreign Language (EFL) learning. Many students struggle to process authentic spoken input due to limited exposure and lack of metacognitive regulation during listening. This study aimed to examine the relationship between Metacognitive Listening Awareness (MLA) and Listening Comprehension among Indonesian EFL high school students through podcast-based listening activities. Using a quantitative correlational design, data were collected from 72 tenth-grade students at SMA Negeri 26 Batam. Two instruments were employed: the Metacognitive Awareness Listening Questionnaire (MALQ) and a podcast-based Listening Comprehension Test (LCT). Statistical analyses included tests of validity, reliability, descriptive statistics, normality, and correlation. Both instruments demonstrated moderate reliability (α = 0.639 for MALQ; α = 0.616 for LCT). The findings revealed no significant correlation between MLA and Listening Comprehension (ρ = –0.103, p = .390), indicating that higher awareness levels did not necessarily predict better comprehension performance. These results suggest that metacognitive awareness alone is insufficient to enhance comprehension without guided strategy instruction and reflective listening practice. The study highlights the importance of integrating metacognitive strategy instruction within authentic, podcast-based learning to foster autonomous and self-regulated EFL learners.